Vehicular cyber physical systems : adaptive connectivity and security - Rawat, Danda B.; Bajracharya, Chandra (Springer, 2016)
This book provides probabilistic, deterministic and geolocation-aware approaches for adaptive connectivity, robust security and privacy-aware communications for vehicular cyber physical systems (CPS). It presents mathematical models and numerical results obtained from experiments and simulations, and a trade-off between connectivity, security and privacy for vehicular communications. Connectivity between vehicles is crucial for vehicular CPS. Intelligent vehicular CPS provides not only road safety and traffic efficiency by exchanging information among vehicles, but also offers infotainment services to passengers using a variety of wireless technologies to forward the traffic/trajectory information with Vehicle-to-Vehicle (V2V), vehicular ad hoc network (VANET), and Vehicle-to-Roadside-to-Vehicle (V2R2V) communications. The book covers how to ensure that the message received from other vehicles is secure and trustworthy, rather than malicious. Further, it reveals how to make sure that the privacy of participants is not revealed while validating the received message. Researchers and professionals working with vehicular networks, smart systems, cyber physical systems, and mobile privacy will find this book valuable.
Keywords: Cooperating objects (Computer systems); Vehicular ad hoc networks (Computer networks); elektronické knihy; electronic books